Interferon autoantibodies as signals of a sick thymus - Oftedal, Bergithe E.; Sjøgren, Thea; Wolff, Anette S. B. (Frontiers in Immunology, 2024)
Type I interferons (IFN-I) are key immune messenger molecules that play an important role in viral defense. They act as a bridge between microbe sensing, immune function magnitude, and adaptive immunity to fight infections, and they must therefore be tightly regulated. It has become increasingly evident that thymic irregularities and mutations in immune genes affecting thymic tolerance can lead to the production of IFN-I autoantibodies (autoAbs). Whether these biomarkers affect the immune system or tissue integrity of the host is still controversial, but new data show that IFN-I autoAbs may increase susceptibility to severe disease caused by certain viruses, including SARS-CoV-2, herpes zoster, and varicella pneumonia. In this article, we will elaborate on disorders that have been identified with IFN-I autoAbs, discuss models of how tolerance to IFN-Is is lost, and explain the consequences for the host.